Do Teachers' Perceptions of High Cultural Responsiveness Predict Better Behavioral Outcomes for Students?. (February 2023) - Fallon, Lindsay M.; Veiga, Margarida B.; Susilo, Annisha; Kilgus, Stephen P.
Teachers' perceptions of high cultural responsiveness in the classroom may be related to positive behavioral outcomes (e.g., higher academic engagement, lower social risk), but little research has explored this possibility. This article addresses this research gap by building upon findings from a preliminary paper in which these relationships were evidenced. Specifically, we present two interrelated follow-up studies. Study 1 examined the relationship between ratings of 20 U.S. teachers on a measure of cultural responsiveness, the Double Check Self-Refection Tool, and students' observed classroom behavior. Results from multilevel modeling indicated that higher Double Check scores significantly predicted higher academic engagement and lower disruptive behavior for 454 students observed. Study 2 investigated the relationship between ratings of 30 U.S. teachers on the Double Check Self-Refection Tool and ratings of 622 students' risk on the Social, Academic, and Emotional Behavior Risk Screener (SAEBRS). Results indicated higher Double Check scores were associated with lower ratings of students' social and emotional risk. Findings also indicated identification as a Black student and a student with a disability predicted teachers' perceptions of higher risk, consistent with previous research. As results remain preliminary, implications include recommendations for additional research and high-quality professional development to promote teachers' cultural responsiveness.